Spatial variation of sub-surface heterogenieties within the dyke swarm of Nandurbar region, Maharashtra, India, for groundwater exploration using Inverse Distance Weighted technique - Khan, Tahama; Baride, Arti; Gupta, Gautam; Erram, Vinit C.; Baride, Mukund V. (My University, 2022)
To understand the protective capacity of aquifers, anisotropic nature and fracture geometry of dyke infested terrain in parts of Nandurbar region, Maharashtra, data from 39 vertical electrical soundings using Schlumberger configuration were acquired. Analysis suggests 3–5 layered structure in the study area. Further, the Dar- Zarrouk and other geoelectric indices were computed utilizing resistivity and layer thickness at each station. The Inverse DistanceWeighted (IDW) algorithmwas used to interpolate data spatially. Longitudinal conductance values suggest that the area has poor to moderate aquifer protective capacity, indicating that weaker zones may be prone to infiltrating contaminants. The high electrical anisotropy (λ) signifies EWand NS oriented dykes, suggesting heterogeneous and anisotropic nature of the subsurface. A direct relationship involving λ and fracture porosity indicate porous medium. The IDWalgorithm, used for the first time in this region, provided an accurate and reliable estimate of spatial distribution and the underlying heterogeneities.
Keywords: ArcGIS; Inverse Distance Weighted; Dar-Zarrouk parameters; Dyke swarm; Nandurbar; India